2013
DOI: 10.4236/ojvm.2013.31007
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Diagnosis of Subclinical African Trypanosoma vivax Infection and Association with Physiological Indices and Serum Metabolites in Extensively Managed Goats in the Tropics

Abstract: Trypanosomosis remains a major challenge to livestock production in much of tropical Sub-Saharan Africa, while diagnosis and treatment still depend on inefficient parasitological techniques. Endemic infections depend on animal reservoirs with subclinical parasitemia. We report molecular diagnosis of subclinical Trypanosoma vivax (T. vivax) infection using polymerase chain reaction (PCR) for the first time in Nigerian goats and associate parasite presence with gross physiological traits and serum metabolites in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…Previous studies of red cells during pregnancy have produced conflicting results, although most have been conducted with goats and cattle, and have demonstrated a decreased number of red blood cells at birth (Earley et al 2013, Sanni et al 2013. However, other studies have demonstrated an increase in the number of red blood cells or hemoglobin levels, and some studies have been unable to verify differences in the erythrocyte counts, packed cell volumes and hemoglobin levels in samples taken during pregnancy compared to those taken immediately after delivery.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies of red cells during pregnancy have produced conflicting results, although most have been conducted with goats and cattle, and have demonstrated a decreased number of red blood cells at birth (Earley et al 2013, Sanni et al 2013. However, other studies have demonstrated an increase in the number of red blood cells or hemoglobin levels, and some studies have been unable to verify differences in the erythrocyte counts, packed cell volumes and hemoglobin levels in samples taken during pregnancy compared to those taken immediately after delivery.…”
Section: Resultsmentioning
confidence: 99%
“…In mammals, respiration is the direct expulsion of carbon dioxide from tissues of the body and elimination of moisture from respiratory tract to help prevent hyperthermia under high ambient temperatures, which is a major adaptive feature of domestic livestock in the hot tropical Africa. The rate of respiration was found to be largely affected by pathogenic T. vivax [35]. The reduction in the respiratory rate of goats infected with pathogenic T. vivax indicates that the infected animals may be more stressed than their non-infected counterpart.…”
Section: The Influence Of Stress On Physiological Haematological Andmentioning
confidence: 96%
“…The reduction in the respiratory rate of goats infected with pathogenic T. vivax indicates that the infected animals may be more stressed than their non-infected counterpart. This is an indication that pathogenic T. vivax could be referred to as stressor in goats and the measurement of respiratory rate is an indication of the physiological alterations of stressed and infected animals as caused by T. vivax [35]. Thermal stressor as a form of environmental heat stress negatively influenced livestock physiological activities especially when an animal is having difficulty in dissipating excess heat load to its environment which subsequently frustrate overall performance e.g.…”
Section: The Influence Of Stress On Physiological Haematological Andmentioning
confidence: 99%
“…The successive outbreak reports from distantly separated regions suggested that T. vivax is presently widespread in former non-endemic regions of Brazilian Semiarid where outbreaks have been reported in dairy cattle and sheep. Although serological surveys suggested that T. vivax was not disseminated in cattle herds in areas where previous outbreaks were controlled by the treatment of all symptomatic animals [ 8 , 9 ], the answer to this question requires extensive surveys using sensitive diagnostic methods in healthy goats, horses and donkeys, which are carriers of T. vivax in Africa [ 10 12 ].…”
Section: Introductionmentioning
confidence: 99%